EDARD: efficient data access based on rumour dissemination in wireless sensor networks. (1st January 2013) - Leila, Kheroua; Samira, Moussaoui; Louiza, Mansour
In this paper, we present a rumour dissemination protocol named: efficient data access based on rumour dissemination (EDARD). EDARD ensures an information uniform distribution to enhance data accessibility in wireless sensor networks. In EDARD, rumours (event occurrences) and queries (requests of information) are disseminated through trajectories as straight as possible preventing backward paths. The straitening trajectory – based on a selective next hop choice and the forking procedure introduced in EDARD protocol have the objective to find data and establish paths to the source event in short delays with fewer transmissions. Simulation and comparison results show that EDARD protocol achieves improvements in terms of query delivery rate, data access time and network traffic.